Lynteris C. (Ed.) (2019), Framing animals as epidemic villains. Histories of non-humans disease vectors, Londres, Palgrave MacMillan, 245 pp. - Rojas, Nicolás Facundo (Universidad Nacional de Quilmes, 2020)
Fil: Rojas, Nicolás Facundo. Universidad Nacional de Lanús. Instituto de Salud Colectiva; Argentina.